2023
DOI: 10.1042/bsr20230819
|View full text |Cite
|
Sign up to set email alerts
|

Increased stiffness of omental arteries from late pregnant women at advanced maternal age

Abstract: Advanced maternal age (≥35 years) is a risk factor for poor pregnancy outcomes. Pregnancy requires extensive maternal vascular adaptations, and with age, our blood vessels become stiffer and change in structure (collagen and elastin). However, the effect of advanced maternal age on the structure of human resistance arteries during pregnancy is unknown. As omental resistance arteries contribute to blood pressure regulation, assessing their structure in pregnancy may inform on the causal mechanisms underlying pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Importantly, despite the mounting evidence and the increased global risk of adverse perinatal outcomes observed, few studies have examined the potential mechanisms underlying this elevated risk in pregnancies of AMA. The work of Wooldridge and colleagues begins to address this gap in the literature [ 7 ] and findings from their recent investigation suggest that maternal resistance arteries collected from pregnant women ≥35 years of age were less compliant and had less elastin than arteries obtained from women <35 years of age. Their findings suggest that alterations in maternal resistance vessel stiffness may contribute to increased risk of adverse maternal and fetal outcomes associated with pregnancy at AMA.…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, despite the mounting evidence and the increased global risk of adverse perinatal outcomes observed, few studies have examined the potential mechanisms underlying this elevated risk in pregnancies of AMA. The work of Wooldridge and colleagues begins to address this gap in the literature [ 7 ] and findings from their recent investigation suggest that maternal resistance arteries collected from pregnant women ≥35 years of age were less compliant and had less elastin than arteries obtained from women <35 years of age. Their findings suggest that alterations in maternal resistance vessel stiffness may contribute to increased risk of adverse maternal and fetal outcomes associated with pregnancy at AMA.…”
Section: Commentarymentioning
confidence: 99%
“…Furthermore, increased vascular stiffness assessed in vivo in early pregnancy is associated with the development of adverse pregnancy outcomes such as preeclampsia [ 14 , 15 ]. In their in vitro approach, Wooldridge et al [ 7 ] obtained omental adipose tissue during scheduled cesarean delivery at term (∼38–39 weeks gestation), isolated omental arteries from this biopsy, and examined collagen and elastin content – the main components of the extracellular matrix within the vascular wall. Previous studies have shown that aging leads to the overproduction of collagen and the degradation of elastin, which contributes to arterial stiffening [ 16 ].…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation